Estrategias de marketing de la plataforma shein y la confianza del consumidor en los productos que comercializa - Moreira Herrera, Kely Naomi (2025)
This project aims to analyze SHEIN's digital marketing strategies, consumer perception of products, and their influence on purchasing decisions. Promotions, discounts, and the use of social media are studied as key tools. A descriptive and correlational field research is conducted under a non-experimental design with qualitative and quantitative methods to obtain a better understanding of the variables. Throughout the research, it was identified that SHEIN managed to establish itself as one of the most influential e-commerce platforms on a global level thanks to the implementation of effective marketing strategies, such as digital advertising and content marketing. Although its popularity had a positive plus, doubts still persist regarding the security, reliability of product transactions, the accuracy of descriptions, and the returns and refunds process. The work also includes techniques such as documentary analysis, observation of the SHEIN mobile application, as well as surveys of the population and an-interview with two digital marketing professionals, in order to understand the reception of this platform.